2013
DOI: 10.3851/imp2749
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lopinavir Concentrations Predict Virological Failure in a Cohort of South African Children Initiating a Protease-Inhibitor-Based Regimen

Abstract: Background Poor adherence to antiretroviral therapy contributes to pharmacokinetic variability and is the major determinant of virological failure. However, measuring treatment adherence is difficult, especially in children. We investigated the relationship between plasma lopinavir concentrations, pretreatment characteristics and viral load >400 copies/ml. Methods A total of 237 HIV-infected children aged 4–42 months on lopinavir/ritonavir oral solution were studied prospectively and followed for up to 52 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…In keeping with our analysis of the pre-randomization phase of the same study 17 , higher LPV concentrations are associated with sustained viral suppression. Our data suggests that children with LPV concentrations >1 mg/L have a reduction in the risk of viremia of about 40%, compared to children with LPV <1 mg/L.…”
Section: Discussionsupporting
confidence: 71%
“…In keeping with our analysis of the pre-randomization phase of the same study 17 , higher LPV concentrations are associated with sustained viral suppression. Our data suggests that children with LPV concentrations >1 mg/L have a reduction in the risk of viremia of about 40%, compared to children with LPV <1 mg/L.…”
Section: Discussionsupporting
confidence: 71%
“…The effect of lopinavir on eryptosis was accompanied by enhanced hemolysis. The concentrations required for the effect are well in the range of plasma concentrations determined in patients under lopinavir treatment [61]. The observed eryptosis and hemolysis may thus well explain the anemia following lopinavir treatment [14].…”
Section: Discussionmentioning
confidence: 52%
“…They observed that with LPV concentrations <1.0 mg/L, the hazard ratio for having HIV RNA >400 copies/mL was 2.3 times higher when compared to LPV concentrations ≥1.0 mg/L [9]. In our study, we found that the odds of having HIV RNA >1000 copies/mL among those with plasma LPV concentrations <1.0 mg/L was 6.47 times when compared to those with plasma LPV concentrations ≥1.0 mg/L.…”
Section: Discussionmentioning
confidence: 99%